Dinotefuran-induced morphophysiological changes in semi-engorged females Rhipicephalus sanguineus Latreille, 1806 (Acari: Ixodidae) ticks: Ultra-structural evaluation - de Oliveira, Patrícia Rosa [UNESP]; Anholeto, Luis Adriano [UNESP]; Bechara, Gerváso Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Elsevier, 2017)
The present study demonstrated the effects of dinotefuran (active ingredient of the acaricide Protetor Pet®) on the ovary and midgut cells of semi engorged R. sanguineus females exposed to different concentrations of this chemical. For this, 120 semi-engorged females were divided into four treatment groups with 30 individuals each: group I or control (distilled water), group II (5000 ppm), groups III (6250 ppm) and group IV (8334 ppm of dinotefuran). All the ticks were immersed in the different concentrations of dinotefuran or in distilled water for 5 min and then dried and kept in BOD incubator for 7 days. The results showed alterations mainly regarding the damaged cell structures, such as yolk granules, organelles and the plasma membrane of the germ cells. In addition, structures related with defense mechanisms were found, such as vacuoles, cytoskeletal filaments, and myelin figures in the germ cells. Damages in the generative cells of the midgut, alterations in the size of digestive cells, the number of endosomes, digestive vacuoles, digestive residues, lipid drops and organelles in the cytoplasm of the digestive cells and the presence of microvilli in the plasma membrane of these cells also demonstrate the progressive damages caused by the action of dinotefuran in the midgut and germ cells of R. sanguineus semi-engorged females. The concentrations applied partially impaired the digestive processes; and, without proper nutrition, all the ectoparasite's physiologic events are prevented from occurring, leading the individual to death. The germ cells were also damaged, and probably would not be able to advance in their development (I–V) and complete the vitellogenesis, which would affect the fertility of the female and consequently impede the formation of a new individual.
Keywords: Acaricide; Control; Dinotefuran; Rhipicephalus sanguineus; Ultrastructure